2019
DOI: 10.1177/1350650119847404
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spinning on the mixed thermal elastohydrodynamic lubrication and fatigue life in point contacts

Abstract: This paper presents a numerical study on the fatigue life for the non-Newtonian mixed thermal elastohydrodynamic lubrication (TEHL) of elliptical contacts with spinning. Sinusoidal surface is used to consider the effect of surface roughness, and the influences of spinning on the mixed TEHL characteristics and fatigue life are investigated. The results show that the temperature, friction coefficient and power loss increase monotonously with the increase of spinning. The spinning motion with moderate velocity is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Therefore, DC-FFT method is applied to improve the speed of convolution [30]. After the all stress components within subsurface were obtained, equivalent stress τ vm could be determined by the following expression [31].…”
Section: Subsurface Contact Stress Field Calculation Methodsmentioning
confidence: 99%
“…Therefore, DC-FFT method is applied to improve the speed of convolution [30]. After the all stress components within subsurface were obtained, equivalent stress τ vm could be determined by the following expression [31].…”
Section: Subsurface Contact Stress Field Calculation Methodsmentioning
confidence: 99%
“…The bearing capacity of the lubricating film should be balanced with the contact load per unit length. 33 where, p = p f + p c, p f and p c are the hydrodynamic pressure and the asperity contact pressure, respectively.…”
Section: Tribo-dynamic Model Of Cam-tappet Pairmentioning
confidence: 99%
“…The authors observed that the non-uniform velocity fields, induced by spin action, can produce a local maximum on the film thickness contours close to the exit constriction of the contact. In a recent study using a thermoelastohydrodynamic (TEHL) model with the consideration of mixed and boundary lubrication, Yan et al [16] also explored the effect of spin, aiming to replicate similar operating conditions as those in Continually Variable Transmissions (CVT). The authors' focus was on the effect of fatigue life induced by any spinning of the contact footprint.…”
Section: Introductionmentioning
confidence: 99%